DOI: 10.1007/978-3-540-79086-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Influenza Drugs: The Development of Sialidase Inhibitors

Abstract: Viruses, particularly those that are harmful to humans, are the 'silent terrorists' of the twenty-first century. Well over four million humans die per annum as a result of viral infections alone. The scourge of influenza virus has plagued mankind throughout the ages. The fact that new viral strains emerge on a regular basis, particularly out of Asia, establishes a continual socio-economic threat to mankind. The arrival of the highly pathogenic avian influenza H5N1 heightened the threat of a potential human pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 172 publications
3
48
1
Order By: Relevance
“…Modifications at the C-5 position of Neu2en5Ac were the first improved in vitro NA inhibitors [9]. However, neither Neu2en5Ac nor the modified compound has an in vivo inhibition activity against IAV, possibly due to their rapid clearance [9]. The presence of Neu2enAc in natural mucins might indicate that hosts also secrete their own NA-inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifications at the C-5 position of Neu2en5Ac were the first improved in vitro NA inhibitors [9]. However, neither Neu2en5Ac nor the modified compound has an in vivo inhibition activity against IAV, possibly due to their rapid clearance [9]. The presence of Neu2enAc in natural mucins might indicate that hosts also secrete their own NA-inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…NA inhibitors such as oseltamivir inhibit viral release by preventing the cleavage of Sias specifically [9]. It has also been shown that NA inhibition with oseltamivir carboxylate suppresses IAV infection of cultured human airway epithelium (HTBE) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, synthetic neuraminidase inhibitors have been shown to suppress influenza virus dissemination (60). To test whether NA antibodies would also interfere with virus spread, MDCK cells were infected with A/chicken/Yamaguchi/7/04 (H5N1) at an MOI of 0.0025 TCID 50 / cell.…”
Section: Na Antibodies Inhibit Virus Spread In Vitromentioning
confidence: 99%
“…3032 The available X-ray crystal structures of viral neuraminidases, 30 bacterial sialidases, 3335 and a more recent human cytosolic sialidase NEU2 36 provide great opportunities for rational sialidase inhibitor design.…”
Section: Introductionmentioning
confidence: 99%